2008
DOI: 10.1061/(asce)0733-9496(2008)134:3(295)
|View full text |Cite
|
Sign up to set email alerts
|

Mixing at Cross Junctions in Water Distribution Systems. II: Experimental Study

Abstract: The present experimental study focuses on the characterization of complex mixing phenomena at pipe intersections within pressurized water distribution networks. To examine the complete mixing assumption at a cross junction, a series of experiments were conducted in the turbulent regime ͑R Ͼ 10,000͒. The experimental setup consists of a cross junction with various sensors, pumps, and a data acquisition system to accurately measure solute concentration. Selected experimental results are compared to computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Methodology for earlier experiments. A number of experiments have been performed to characterize the mixing behavior within individual pipe joints (Austin et al, 2008; McKenna et al, 2007; O'Rear et al, 2005). Pumps were used to supply water through pipes joined by a cross junction.…”
Section: Description Of Physical Mixing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodology for earlier experiments. A number of experiments have been performed to characterize the mixing behavior within individual pipe joints (Austin et al, 2008; McKenna et al, 2007; O'Rear et al, 2005). Pumps were used to supply water through pipes joined by a cross junction.…”
Section: Description Of Physical Mixing Processesmentioning
confidence: 99%
“…Water distribution analysis software such as EPANET (Rossman, 2000) typically assumes complete and instantaneous mixing within a junction such that the outlet concentrations are all equal. However, recent studies have shown that flow in cross junctions can result in incomplete mixing under a wide range of conditions (Austin et al, 2008; Ho, 2008; Romero‐Gomez et al, 2008; Ho et al, 2007, 2006; McKenna et al, 2007; Webb & van Bloemen Waanders, 2006; O'Rear et al, 2005; van Bloemen Waanders et al, 2005). Impinging flows within a cross junction tended to bifurcate and reflect off one another rather than mix completely.…”
mentioning
confidence: 99%
“…The conventional assumption of perfect mixing at junctions has been studied with measurements and Computational Fluid Dynamics modelling (Austin et al, 2008;Romero-Gomez et al, 2008a). The studies showed that at T-junctions, that are at least a few pipe diameters apart, perfect mixing can be assumed, while in cross junctions less than 10% mixing may occur.…”
mentioning
confidence: 99%
“…They employed the simulator approach by Rossman [47] as a tool that assumes an idea mixing at all nodes. However, the investigation by Austin et al [136] revealed that the proposition generated an invalid result. This led to the development of an adjoint theory by Wang et al [137], which incorporates incomplete mixing at the junction.…”
Section: Simulation-optimisation Approachmentioning
confidence: 99%